PENENTUAN UKURAN OPTIMUM KAPASITOR BANK DAN DUMMY LOAD PLTMH DENGAN GENERATOR INDUKSI - Andi Setiawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2013)
A technique of determining the size of the capacitor and dummy load for hydroelectric power generation system that uses an induction machine as generator is done by creating a model of the components and systems in Matlab and prepare the scenario of loading and setting of system parameters in order to obtain the size of the capacitor and dummy load were optimum at once . The simulation results can already provide information about the size of all these component sizes and once inform the maximum active power limit that can be borne by the generator . In this paper the assignment scenario is purely resistive load and therefore has not investigated whether the method could also be used to determine the size of the components of a system in which there are inductive loads . Keywords: Capacitor Bank, PLTMH, Asynchronous Generator